Quantum annealing for the adjuster routing problem - Mori, Naoya; Furukawa, Satoshi (Frontiers in Physics, 2023)
In the event of a disaster such as an earthquake, insurance companies basically conduct on-site witnessing. Depending on the scale of the disaster, hundreds of adjusters are dispatched from each office to the affected buildings per day. In such cases, it must be determined which adjusters are to witness which buildings and in which order and the route must be optimized to conduct efficient witnessing. In this paper, we define this witnessing route decision as an optimization problem and propose the Adjuster Routing Problem (ARP). The ARP can be viewed as the extension of the Vehicle Routing Problem (VRP). In fact, we introduce constraints that are not to be considered in the usual VRP, such as adjuster-building matching and satisfying the desired time. The VRP is known as NP-hard optimization problem and is considered difficult to solve on a classical computer. Therefore, we formulated various constraints in QUBO so that quantum annealing can be applied to the ARP. In addition, we also conduct numerical experiments with D-Wave. The ARP is a realistic problem and our research provides a new example of applications of quantum annealing to the real-world problem.